The role of the teacher and learning in clinical practicum scales: A psychometric testing of the Finnish versions - Strandell-Laine Camilla; Haapa Toni; Timonen Leena; Suikkala Arja (WILEY, 2025)
Aim: To test the psychometric properties of the further developed Role of the Teacher (Tc2) and the new Learning in Clinical Practicum (LCP) scales in a sample of Finnish healthcare students.
Design: Psychometrical testing of the Tc2 and LCP scales.
Methods: A sample consisting of 1133 healthcare students completed the further developed Tc2 scale and the new LCP scale between January and June 2020. Statistical data analysis was performed using explorative factor analysis and Cronbach's alpha coefficient. The STROBE checklist for cross-sectional studies was applied in reporting.
Results: Both the further developed Tc2 and the new LCP scales were shown to be valid and reliable. Explorative factor analysis confirmed a two-factor solution for the Tc2 scale with a 76.3% explained variance and a one-factor solution for the LCP scale with a 58.0% explained variance. The scales' internal consistency reliabilities were high (0.9).